Banana ale a plant design on processing of a specialty beer - d'Hulst, Dirk (College of Engineering, 1995)
Main product: Banana ale -- Main raw materials: Malt, hops, water, bananas -- Plant location: Iligan, Lanao del Norte -- Plant area: 4,500 sq.ft. -- Annual volume of production: 528,000 liters -- Annual sales: Php 8,250,000.00 first year -- Annual income (after tax): Php 585,227.62 first year -- Total capital investment: Php 6,000,000.00 -- Product unit cost (320 mL bottle, yr.1): P 2.71 -- Suggested product selling price (Yr.1): P 5.50 -- Average rate of return on investment (ROI): 11.8% -- Payback period (from Pro Forma): 3.2 years -- Breakeven capacity (P.A.): 495,000 liters